2019
DOI: 10.1186/s12870-019-1633-1
|View full text |Cite
|
Sign up to set email alerts
|

Soybean (Glycine max L. Merr.) seedlings response to shading: leaf structure, photosynthesis and proteomic analysis

Abstract: BackgroundIntercropping and close planting are important cultivation methods that increase soybean yield in agricultural production. However, plant shading is a major abiotic stress factor that influences soybean growth and development. Although shade affects leaf morphological parameters and decreases leaf photosynthesis capacity, information on the responses of soybean leaf photosynthesis to shading at proteomic level is still lacking.ResultsCompared with leaves under normal light (CK) treatment, leaves unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 41 publications
3
57
0
7
Order By: Relevance
“…For example, when exposed to shade stress from neighboring plants, plants adapted to open ranges (e.g. Arabidopsis, rice and soybean) can develop shade avoidance response, leading to shade avoidance syndrome [60][61][62]. Shade avoidance response is conducive to survival of the plant under shade conditions [61,63].…”
Section: Discussionmentioning
confidence: 99%
“…For example, when exposed to shade stress from neighboring plants, plants adapted to open ranges (e.g. Arabidopsis, rice and soybean) can develop shade avoidance response, leading to shade avoidance syndrome [60][61][62]. Shade avoidance response is conducive to survival of the plant under shade conditions [61,63].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of environmental stress on photosynthesis of medicinal plants include regulating the stomatal size and causing damage to the PSII reaction center (Berry and Downton 1982). Previous studies showed that the effects of shading conditions on photosynthesis of different medicinal plants were different (Wang et al 2017, Tafoya et al 2018, Fan et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…[21]. Previous studied have reported that sprouts, leaves and seeds of soybean and mung bean contain high amounts of crude proteins, amino acids, lipids and minerals [22][23][24]. They have been shown to possess antioxidant, antimicrobial, anti-inflammatory, antidiabetic and antihypertensive effects [23].…”
Section: Discussionmentioning
confidence: 99%